Analisa Rasio Laporan Keuangan Untuk Menilai Kinerja Perusahaan PT Ace Hardware Indonesia Tbk - Denny Erica; Hoiriah Hoiriah; Mulyadi Mulyadi (Akasia: Artikel Ilmiah Sistem Informasi Akuntansi, 2021)
Abstract - PT Ace Hardware Indonesia Tbk was founded in 1995 and is engaged in household and lifestyle equipment business, with 208 outlets spread across 49 cities and 27 provinces. The company has been listed as an issuer on the Indonesia Stock Exchange since 2007 with the exchange code "ACES". The company made a 30% share offering to the public and currently the company's free float shares have reached 40%. Companies can use ratio analysis to their financial statements to assess company performance. As for the data method used in this study using the method of observation and literature study related to the financial data of PT Ace Hardware Indonesia Tbk, which is analyzed using the calculation of economic arithmetic ratios related to company performance. The results of the analysis of the financial statements consist of the Liquidity Ratio, Leverage Ratio, Activity Ratio, and Profitability Ratio, so that the company has the ability to be able to determine and make management decisions related to company performance. Keywords: Ratio Analysis, Financial Statements, Company Performance